PENYULUHAN TINDAK PIDANA PENYEBARAN BERITA HOAX MELALUI MEDIA SOSIAL DI KALANGAN GENERASI MUDA PADA MAHASISWA FAKULTAS HUKUM UNIVERSITAS DARMA AGUNG MEDAN - Ria Sintha Devi; Rudolf silaban; Nanci Yosepin Simbolon (Jurnal PKM Hablum Minannas, 2022)
The development of information and communication technology was then responded by the government by issuing a law. Media managers in Indonesia are still developing their abilities in an effort to face the new world and provide excellent programs that suit the needs of the community, especially young people. This activity will conducted through face-to-face meetings attended by students of the Faculty of Law, Darma Agung University, social media on the one hand is private. An account belonging to someone on social media, such as Facebook, is interpreted as a substitute for that person's appearance in cyberspace which contains information about the owner, such as name and photo and identity to other privacy, spreading false and misleading news that results in consumer losses in electronic transactions and disseminating information aimed at causing hatred or hostility to certain individuals and/or community groups based on ethnicity, religion, race, and inter-group (SARA). Finally, a person can be punished for sending electronic information and/or electronic documents that contain threats of violence or intimidation aimed at personally